Kerusakan Tanaman Selada (Lactuca sativa L) oleh OPT pada Budidaya Hidroponik di Kota Semarang - Kusuma, Marsliana Indah; Orbit, Juwan; Safira, Wahyu Ida; Zuhri, Nur Muttaqien; Ayomi, Nun Maulida Suci (Universitas Muhammadiyah Semarang, 2024)
Hydroponic plants are plants that grow using nutrient solutions that contain minerals needed for plant growth. This study was conducted to identify various types of pests that attack mustard and lettuce plants grown in a hydroponic system. The research location was in Mijen Sub-district, Semarang City. Data collection methods used included surveys, interviews, and direct observation in the field which were then analysed descriptively. Observations of pests and diseases were conducted routinely every week until harvest time. Observations from the research location showed that the largest pest population came from the order Diptera (Fruit Flies) with 48 individuals, followed by the order Lepidoptera (Moths) with 33 individuals. Meanwhile, the population of pests from the Hemiptera and Hymenoptera orders (Walang sangit and Honey Bee) had the same number, 18 and 6 respectively.